Legend of Phra Ruang in Nakhon Thai Valley: From Local Legend to Explaining National History - Sankom, Teerawatt (Asian Journal of Traditional and Innovative Arts and Textiles, 2023)
The article based on the objective of studying about the legend of Phra Ruang that appeared in the Nakhon Thai Valley in Nakhon Thai District, Phitsanulok Province from documents with historical methods. The findings are as following; in the Nakhon Thai Valley there are legends of Phra Ruang that describe the origins of the physical characteristics of various places in many expressions. After that, there was an effort by a group of people to connect the legend of Phra Ruang with the historical development of the Thai nation. Especially the interpretation that Phra Ruang is Phra Khun Sriinthrathit chief of Muang Bang Yang which is believed to be the original name of Muang Nakhon Thai. Until the story of Phra Ruang in the Nakhon Thai Valley was re-explained through the story of Pho Khun Sri Intharathit King of Sukhothai instead of being a local cultural hero.